Resource-Efficient Wood Lightweight Concrete Composites in Building Constructions. Issue 2 (1st May 2017) - Fadai, Alireza; Winter, Wolfgang
Abstract: With the aim to optimize energy efficiency and ecological characteristics of structural building components, through several research projects, the Department of Structural Design and Timber Engineering (ITI) at the Vienna University of Technology (VUT) developed several wood-based composite systems, which combine timber products with other conventional building materials and components. As a representative example for these developments, the application of wood lightweight concrete (WLC) composites illustrates the extent of inter-relationships in the development of complex system solutions when focusing on the increase of resource efficiency. The aim is to develop a multi-layer building construction composed of WLC and connected timber sections to gain and make use of advantages of each of the material used—light weight, thermal storage and insulation, economic and ecological benefits. By using renewable resources, waste products from the forest industry and manufactured wood products, this technology provides statically and energy-efficient components for low-energy constructions. Such products support rapid-assembly construction methods, which use prefabricated elements.